2005
DOI: 10.1002/humu.20142
|View full text |Cite
|
Sign up to set email alerts
|

Cone cGMP-gated channel mutations and clinical findings in patients with achromatopsia, macular degeneration, and other hereditary cone diseases

Abstract: Unrelated patients with achromatopsia, macular degeneration with onset under age 50 years, cone degeneration or dysfunction, cone-rod degeneration, or macular malfunction were screened for mutations in the three genes known to be associated with achromatopsia: the GNAT2 gene encoding the alpha subunit of cone transducin and the CNGA3 and CNGB3 genes encoding the alpha and beta subunits of the cone cGMP-gated cation channel. We found no examples of patients with GNAT2 mutations. Out of 36 achromats, 12 (33%) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 32 publications
3
98
0
3
Order By: Relevance
“…Therefore, we argue that there is no difference between the 15 Hz ERGs of an achromat and normal subjects for low flash strengths and that the primary and secondary rod pathways function normally. In the literature, the functioning of the rods in achromatic patients is generally described as normal [32][33][34][35][36], although recently, abnormalities in rod driven ERGs have also been reported [37,38]. Therefore, it would be interesting to measure 15 Hz ERGs in more patients with achromatopsia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we argue that there is no difference between the 15 Hz ERGs of an achromat and normal subjects for low flash strengths and that the primary and secondary rod pathways function normally. In the literature, the functioning of the rods in achromatic patients is generally described as normal [32][33][34][35][36], although recently, abnormalities in rod driven ERGs have also been reported [37,38]. Therefore, it would be interesting to measure 15 Hz ERGs in more patients with achromatopsia.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In preparation for translation to human clinical trials, it will be important to be able to identify the best candidates who still have intact retinal architecture and may best benefit from genetic therapy as well as to develop objective tools for monitoring safety and efficacy. Initial studies using lower-resolution time-domain optical coherence tomography (OCT) have shown some general changes in macular thickness, 16,17 but subsequent higherresolution spectral-domain (SD) OCT devices have revealed changes in foveal architecture that suggest achromatopsia is a progressive disease that worsens with age. [18][19][20][21] Additional studies are required to determine whether retinal architecture is indeed more preserved at an earlier age, but only cooperative adults and older children are able to be imaged on conventional SD-OCT systems.…”
mentioning
confidence: 99%
“…Naturally occurring mutations in genes encoding CNGA3 and CNGB3 are highly associated with human cone diseases, including achromatopsia, progressive cone dystrophy, and early-onset macular degeneration (7)(8)(9). Indeed, Ͼ70 disease-associated mutations have been identified in CNGA3 and CNGB3 (8,9), and these mutations account for Ͼ70% of achromatopsia patients (7,8).…”
mentioning
confidence: 99%
“…Indeed, Ͼ70 disease-associated mutations have been identified in CNGA3 and CNGB3 (8,9), and these mutations account for Ͼ70% of achromatopsia patients (7,8). Achromatopsia is a devastating hereditary visual disorder, characterized by deficient cone-mediated electroretinographic (ERG) responses, color blindness, visual acuity loss, pendular nystagmus, extreme light sensitivity, and daytime blindness.…”
mentioning
confidence: 99%